EVALUATING THE EFFECTIVENESS OF TREATMENT METHODS FOR REFRACTIVE AMBLYOPIA IN CHILDREN - Boboeva , Ra'nо Rakhimovna (Educational Research in Universal Sciences, 2023)
In three cases, in the treatment of refractive amblyopia in the children’s department of the Bukhara Regional Ophthalmological Hospital, the device MACDEL-08 "Speckle" was used and its results were studied. 35 patients aged 7-18 years were examined in the outpatient clinic. Examination of children was carried out according to standard plans, and groups of outpatients used methods of lymphostimulation, laser stimulation. The pre- and post-treatment results were analyzed to evaluate treatment outcomes.